The Use of Different Components of Brain Oxygenation for the Assessment of Cerebral Haemodynamics: A Prospective Observational Study on COVID-19 Patients - Robba, Chiara; Cardim, Danilo; Ball, Lorenzo; Battaglini, Denise; Dabrowski, Wojciech; Bassetti, Matteo; Giacobbe, Daniele Roberto; Czosnyka, Marek; Badenes, Rafael; Pelosi, Paolo; Matta, Basil, The GeCovid group; et al. (Frontiers in Neurology, 2021)
Introduction: The role of near-infrared spectroscopy (NIRS) for the evaluation of cerebral haemodynamics is gaining increasing popularity. The primary aim of this study was to assess the correlation of the different components of regional cerebral oxygenation (rSO2)-measured by NIRS as indirect surrogates of cerebral blood flow (CBF)-with an established technique for non-invasive CBF assessment, Transcranial Doppler (TCD). Secondary aim was to investigate which component of rSO2 is a better predictor of CBF in response to hemodynamic changes. Methods: Mechanically ventilated patients with COVID-19 admitted to the Intensive Care Unit (ICU) of San Martino Policlinico, Genova, Italy during the second wave of the pandemic and who underwent multimodal neuromonitoring (including NIRS and TCD) were included. rSO2 and its components (relative changes in arterial-oxyhemoglobin, O2Hbi, venous-deoxyhemoglobin,HHbi and total haemoglobin, cHbi) were compared with CBF-based TCD (measured through cerebral blood flow velocity of the middle cerebral artery, CBFV). Changes (Δ) in CBFV and rSO2, O2Hbi, HHbi and cHbi after systemic arterial blood pressure (MAP) changes following different maneuvres (i.e. rescue therapies and haemodynamic manipulation) were assessed as percentage changes from baseline (Δ%). Results: One hundred and four measurements from 25 patients were included. Significant effects of ∆%MAP on ∆%CBF were observed after different maneuvers for CBFV, ∆cHbi and ∆O2Hbi. The highest correlation was found between ΔCBFV and ΔO2Hbi (R=0.88, p<0.0001), and the poorest between ΔCBFV and ΔHHbi (R=0.34, p=0.002). Conclusions: The use of indexes derived from the different components of rSO2 can be useful for the bedside evaluation of cerebral haemodynamics in critically ill patients undergoing rescue therapies.